2018
DOI: 10.1038/s41598-018-24243-z
|View full text |Cite
|
Sign up to set email alerts
|

Environment-dependent striatal gene expression in the BACHD rat model for Huntington disease

Abstract: Huntington disease (HD) is an autosomal dominant neurodegenerative disorder caused by a mutation in the huntingtin (HTT) gene which results in progressive neurodegeneration in the striatum, cortex, and eventually most brain areas. Despite being a monogenic disorder, environmental factors influence HD characteristics. Both human and mouse studies suggest that mutant HTT (mHTT) leads to gene expression changes that harbor potential to be modulated by the environment. Yet, the underlying mechanisms integrating en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…New data are constantly emerging regarding transcriptional dysregulation in HD, both from human brain and from mouse models [30,58,[261][262][263][264][265][266][267]. Although as discussed above, specific transcription factors (TFs) are implicated, e.g., Foxp2 [82], it is unlikely that HD transcriptional pathology can be attributed to any single TF.…”
Section: Transcriptional Alterationsmentioning
confidence: 99%
“…New data are constantly emerging regarding transcriptional dysregulation in HD, both from human brain and from mouse models [30,58,[261][262][263][264][265][266][267]. Although as discussed above, specific transcription factors (TFs) are implicated, e.g., Foxp2 [82], it is unlikely that HD transcriptional pathology can be attributed to any single TF.…”
Section: Transcriptional Alterationsmentioning
confidence: 99%
“…It is widely believed that environmental exposures contribute to the vast majority of sporadic Alzheimer’s, Parkinson’s, Huntington’s and prion diseases alone or via interactions with genetic factors [45,46,47,48,49]. Epidemiological studies have associated environmentally persistent organic pollutant exposure to brain disorders [46].…”
Section: Contribution Of Environmental Factors To Amyloid Diseasementioning
confidence: 99%
“…HD patients might be exposed to both endogenous and exogenous glycolipid antigens capable of activating iNKT cells [2123]. Thus, we wanted to determine whether activation of iNKT cells can impact the pathogenesis of HD in R6/2 Tg mice.…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous [22] and exogenous [21] glycolipid antigens can activate iNKT cells in a CD1d-dependent manner. Moreover, enterogenous glycolipids derived from commensal bacteria circulate throughout the body and can also be recognized by iNKT cells [23]. It has been reported that microbial metabolites play a critical role in shaping the development and function of host immune responses [37].…”
Section: Discussionmentioning
confidence: 99%